2013
DOI: 10.5194/acpd-13-5601-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global sea-to-air flux climatology for bromoform, dibromomethane and methyl iodide

Abstract: Volatile halogenated organic compounds containing bromine and iodine, which are naturally produced in the ocean, are involved in ozone depletion in both the troposphere and stratosphere. Three prominent compounds transporting large amounts of marine halogens into the atmosphere are bromoform (CHBr<sub>3</sub>), dibromomethane (CH<sub>2</sub>Br<sub>2</sub>) and methyl iodide (CH<sub>3</sub>I). The input of marine halogens to the stratosphere is based on obse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 72 publications
3
40
1
Order By: Relevance
“…IO, OIO, I 2 ) species (SaizLopez et al, 2012b). Recent measurements from aircraft (Dix et al, 2013;Wang et al, 2015), balloons (Butz et al, 2009), mountain tops (Puentedura et al, 2012), ground stations (Lawler et al, 2014;Mahajan et al, 2010;Read et al, 2008), and cruises (Großmann et al, 2013;Jones et al, 2010;Mahajan et al, 2012) have enabled the development of global organic halogen emissions Ziska et al, 2013) and, more recently, data sets of IO observations with extensive geographical coverage (PradosRoman et al, 2015b;Wang et al, 2015).…”
Section: T Sherwen Et Al: Iodine's Impact On Tropospheric Oxidants:mentioning
confidence: 99%
“…IO, OIO, I 2 ) species (SaizLopez et al, 2012b). Recent measurements from aircraft (Dix et al, 2013;Wang et al, 2015), balloons (Butz et al, 2009), mountain tops (Puentedura et al, 2012), ground stations (Lawler et al, 2014;Mahajan et al, 2010;Read et al, 2008), and cruises (Großmann et al, 2013;Jones et al, 2010;Mahajan et al, 2012) have enabled the development of global organic halogen emissions Ziska et al, 2013) and, more recently, data sets of IO observations with extensive geographical coverage (PradosRoman et al, 2015b;Wang et al, 2015).…”
Section: T Sherwen Et Al: Iodine's Impact On Tropospheric Oxidants:mentioning
confidence: 99%
“…There are different approaches in creating global bromoform emission inventories. In the bottom-up approach, emissions are extrapolated from marine and atmospheric observations in different locations (Quack and Wallace, 2003;Butler et al, 2007;Palmer and Reason, 2009;Ziska et al, 2013). The topdown approach uses chemistry transport and chemistry climate models to infer possible emission distributions that reproduce observed atmospheric abundances of VSLSs Liang et al, 2010;Ordóñez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low ozone values observed in the upper troposphere in this region, low OH values and a low oxidation capacity are expected in this region resulting in prolonged lifetimes of many trace species (Kley et al, 1996;Solomon et al, 2005;Rex et al, 2014). Hossaini et al (2013) used their 3-D chemical transport model to evaluate a range of different emission inventories Liang et al, 2010;Ziska et al, 2013). For this purpose the model outputs for the different emission inventories were compared to independent atmospheric observations including the SHIVA aircraft data, and revealed that significant differences in these scenarios exist for many geographical regions including the western Pacific region.…”
Section: Introductionmentioning
confidence: 99%